The impact of Mindfulness and Mental Skills Protocols on Athletes' Competitive Anxiety - Dana Amir; Shahir Vesal Alipour; Ghorbani Saeed (Sciendo, 2022)
Study aim: This study aims at examining the impact of Mindfulness and mental skills on competitive anxiety in athletes.